ABOUT THE CLOSURE OF THE MOSCOW DIOCESAN COUNCIL - N.A. Krivosheeva (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article contains unknown documents about the closure of the MoscowDiocesan Council in 1921, there is His Holiness Patriarch Tikhon's circular letterinstructing Diocesan Councils as to what steps should be taken in case of their abolish(ment, a report of the NkaU expert Shpitsberg concerning the closure of the MoscowDiocesan Council. (Рublication and commentaries by N.A. Krivosheeva.)